2010
DOI: 10.1159/000313491
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Carbon Adsorbent (AST-120) Protects Deterioration of Renal Function in Chronic Kidney Disease Rats through Inhibition of Reactive Oxygen Species Production from Mitochondria and Reduction of Serum Lipid Peroxidation

Abstract: Background/Aim: An imbalance in renal redox status contributes to progression of renal dysfunction. We investigated the effects of an oral charcoal adsorbent (AST-120) on renal redox status, superoxide production from renal mitochondria, and serum lipid peroxidation using chronic kidney disease (CKD) model rats. Methods: CKD was induced by 5/6 nephrectomy. CKD rats were divided into 2 groups: controls, and those treated with AST-120 for 20 weeks. We evaluated: (1) renal redox status by in vivo low-frequency el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Furthermore, oxidative stress is one of the major mechanisms responsible for the toxic effects of protein-bound uremic toxins [7,15]. Therapy with AST-120 in both clinical and animal studies can suppress oxidative stress in renal failure [23,32]. Our study for the first time presents that AST-120 can decrease the MDA level in dialysis patients.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, oxidative stress is one of the major mechanisms responsible for the toxic effects of protein-bound uremic toxins [7,15]. Therapy with AST-120 in both clinical and animal studies can suppress oxidative stress in renal failure [23,32]. Our study for the first time presents that AST-120 can decrease the MDA level in dialysis patients.…”
Section: Discussionmentioning
confidence: 75%
“…104 Indoleacetic acid in particular had a pronounced negative impact on 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide reduction, and high-resolution respirometry showed that this solute diminished the maximum capacity of the electron transport system, signifying a reduction in the reserve capacity of the oxidative phosphorylation system. 104 In addition, Owada et al 105 showed that indoxyl sulfate increased the production of superoxide and hydroxyl radicals in rat kidney mitochondria, and Dzurik et al 106 reported that hippuric acid reduced ammonia production by P-dependent mitochondrial glutaminase in kidney homogenates from rats, thereby shifting ammonia production from mitochondria to the lumen of proximal tubules. In addition, reduced functioning of hepatic mitochondria after exposure to dialysate and p-cresol have been reported previously.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 99%
“…In addition, oAC has extensive effects on immune and inflammatory processes. It can absorb endotoxin‐induced cytokines and reduce the production of tumour necrosis factor (TNF) and interferon c (IFNc), 20 it was proved to improve renal function 22 …”
Section: Discussionmentioning
confidence: 99%